Erectile Dysfunction in Euthymic Patients with Bipolar Disorder (Journal of Psychiatrists' Association of Nepal, 2026)
Background: Bipolar disorder (BD) affects ~1% of the global population, yet erectile dysfunction (ED) during euthymia remains poorly understood, particularly in Nepal, where cultural taboos suppress discussion of sexual health. This study aimed to identify clinical and socio-demographic correlates of ED among euthymic male patients with bipolar disorder.Material and methods: We conducted a cross-sectional study at Mental Hospital, Lagankhel, Nepal, recruiting 185 euthymic males of age 18-60 years through outpatients via convenience sampling. Euthymia was confirmed using Young's Mania Rating Scale